Differential Mechanisms of Ang (1-7)-Mediated Vasodepressor Effect in Adult and Aged Candesartan-Treated Rats - S. Bosnyak; R. E. Widdop; K. M. Denton; E. S. Jones (International Journal of Hypertension)
Angiotensin (1-7) (Ang (1-7)) causes vasodilator effects in Wistar-Kyoto (WKY) rats and spontaneously hypertensive rats (SHRs) via angiotensin type 2 receptors (AT2R). However, the role of vascular AT2R in aging is not known. Therefore, we examined the effect of aging on Ang (1-7)-mediated vasodepressor effects and vascular angiotensin receptor localization in aging. Blood pressure was measured in conscious adult (~17 weeks) and aged (~19 months) normotensive rats that received drug combinations in a randomised fashion over a 4-day protocol: (i) Ang (1-7) alone, (ii) AT1R antagonist, candesartan, alone, (iii) Ang (1-7) and candesartan, or (iv) Ang-(1-7), candesartan, and the AT2R antagonist, PD123319. In a separate group of animals, the specific MasR antagonist, A779, was administered in place of PD123319. Receptor localisation was also assessed in aortic sections from adult and aged WKY rats by immunofluorescence. Ang (1-7) reduced blood pressure (~15 mmHg) in adult normotensive rats although this effect was dependant on the background dose of candesartan. This depressor effect was reversed by AT2R blockade. In aged rats, the depressor effect of Ang (1-7) was evident but was now inhibited by either AT2R blockade or MasR blockade. At the same time, AT2R, MasR, and ACE2 immunoreactivity was markedly elevated in aortic sections from aged animals. These results indicate that the Ang (1-7)-mediated depressor effect was preserved in aged animals. Whereas Ang (1-7) effects were mediated exclusively via stimulation of AT2R in adult WKY, with aging the vasodepressor effect of Ang (1-7) involved both AT2R and MasR.